Energy theory of periodic economic growth - Bejan, Adrian; Errera, Marcelo R.; Gunes, Umit (WILEY, 2020)
This article shows that the sudden end of economic expansion (movement, wealth) emerges as a natural, physical feature of the spreading movement, which has access to power (money), freedom to morph, and power storage (savings) for future movement on even greater areas. The movement is driven by power generation, which is interspaced with power savings on the same area. The theory is constructed systematically from the physical basis of economics concepts (money, savings, time, and bubbles) to a physics model that accounts for the time-dependent spreading of movement on an area. Previous study has shown that physics accounts for the proportionality between the annual wealth (GDP) of a population and the annual consumption of fuel to generate power for that population. The present theory extends this view to the more realistic situation where every movement in society (wealth and fuel consumption) is time dependent.
Keywords: crises; economic bubbles; economic cycles; growth; power storage; thermodynamics; CONSTRUCTAL LAW; ADRIAN BEJAN; SUSTAINABILITY ASSESSMENT; EVOLUTION; DESIGN; PHYSICS; GENERATION; SYSTEMS; DEMAND; Energy & Fuels; Nuclear Science & Technology